Embedding Micro-Credential Concept in Financial Management Modular Course - Norazidah, Shamsudin; Awanis, Romli; Airin, Abdul Ghani; Fadzida, Ismail (Penerbit UPM, 2022)
Micro-Credential is currently a new culture in offering training and short-courses in Malaysia. Following the Covid-19 pandemic outbreak, many Micro-Credentials have been developed and offered, and applicants have various choices whether to enroll from local or international provider. Micro-Credentials give the flexibility for the participants to acquire knowledge and skills at their own convenient pace, place and time. Due to these advantages and the similar objective of Micro-Credential method, the concept has been embedded into a Modular Course on Module 3 of Financial Management. The objective is to expose students to experience the concept of Micro-Credential learning experience as advancement to a blended learning method and to analyze the students’ performance before and after the concept was applied. Two analyses have been made [1] Comparing students’ performance on the same assessment in different semesters (Test on Module 3); [2] Comparing students’ performance on different assessments in the same semester (Quiz on Module 1 vs. Test on Module 3). The first analysis found that the performance of the students increased significantly from 50.40% to 77.45% whereas in the second analysis, the result also shows better performance from 74.6% to 77.45%, in which historically, the result would usually be lower. Therefore, it can be concluded that the concept of Micro-Credential has a positive impact in this Modular Course. It is suggested that educators could explore and embed the Micro-Credential concept as part of their teaching and learning delivery method as an advancement to the substitute blended learning mode.